Learning Environment in the Optics of Critical Constructivism - Anna Perkowska-Klejman; Anna Górka-Strzałkowska (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction:This article is an attempt to show the constructivist learning environment as a model, as a concept that assumes that the student is an active, not a passive participant in the process of gaining in-depth, flexible and systemic knowledge rather than fragmentary, rigid or mechanically reproduced. The text focuses on the contemporary needs of students based on radical and social constructivism. The main dimensions of critical constructivism and elements of a constructivist learning environment are outlined based on Peter Taylor and Barry Fraser's concept. Research Aim:The aim is to show critical constructivism as a set of various theories, concepts creating conditions for independent construction of knowledge and creating a friendly-learning environment. Evidence-based Facts:The concept is derived from the teaching imperative (John Dewey, Jean Piaget, Lev Vygotsky and Howard Gardner). It assumes that learning is an active process of constructing knowledge based on the experience of the learner and such construction is usually completed subjectively and metacognitively). The concept of constructivism is quite often used by both theoreticians (academic lecturers and researchers) as well as practitioners (school teachers). Summary: In the article, we analyze the role played by a constructivist learning environment that radically questions the vision of a student as a passive recipient and gives him the status of an active subject contributing to the construction of a learning-friendly environment. Education should be seen as supporting the student in the process of creating meanings that allow to construct your own understanding of the world.